Information System Security of Indonesia Terrestrial Border Control - Tjiptabudi, Fransiskus Mario Hartono; Bernardino, Raul (Bina Nusantara University, 2019)
Today, Information Technology (IT) becomes an integral part of human life. IT boosts every sector, such as infrastructure, economics, agriculture, social, organization, and politics. The institutional systems are developed according to the specific business requirements, processes, flows, and security. Pos Lintas Batas Negara ‘integrated cross-border post’ (PLBN) is a designated authority consisting of the Custom, Immigration, and Quarantine (CIQ). Each section has a different Standard Operation Procedure (SOP). This research aims to develop a secure information system based on Confidentiality, Integrity, and Availability (CIA) concepts. The CIA is embedded in the ISO 27001 and McCumber Cube approach. The research focuses on the Secure Immigration Information System (SIIS). This research is conducted in the Wini immigration office. The researchers observe the immigration activities on the location, interview the immigration officers, and collect information. The researchers produce an effective, efficient, and security application prototype system.